Zat Pengatur Tumbuh NAA (Naphtaleine Acetic Acid) dan BAP (6-Benzyl Amino Purine) serta Air Kelapa untuk Menginduksi Organogenesis Tanaman Anthurium (Anthurium andraeanum Linden Ex Andre) - Dyah Prihatmanti; Nurhayati Ansori Mattjik (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
purpose of this experiment was to investigate the effect of plant growth regulators NAA, HAP, and coconut , water in Anthurium andraeaum propagation by tissue culture. The experimental design was factorial arranged in randomized block design. First factor was NAA concentration consisted of 0.0 mg/l, 0.1 mg/l, 0.2 mg/l. Second factor was HAP concentration consisted of 0 mg/l, 1 mg/l, 2 mg/l. Third factor was coconut water consisted of 0%. 10%, 20%, 30%. Response of survive explant was callus formation especially on NAA 0.2 mg/l. HAP 1 mg/l and 2 mg/l resulted greening callus followed by shoots formation. Coconut water 0, 10, and 20% could promote culture growth. The combination of treatment coconut water 0%, 10%, NAA 0.2 mg}J, and HAP 1 mg/l and 2 mg/l stimulated embriogenesis of callus to be shoots, leaves and roots. Key words : Anthurium andraeanum, NAA (Naphtaleine Acetic Acid), HAP (6-Henzyl Amino Purine)